Kajian Yuridis Kriminologis Terhadap Pemalsuan Surat Keterangan Domisili Pada Pendaftaran Peserta Didik Baru Dalam Sistem Zonasi Di Kota Bandung - Vira Annisa; Dian Andriasari, S.H.,M.H (Bandung Conference Series: Law Studies, 2022)
Falsification of Domicile Certificates on the registration of new learners with a zoning system is a form of crime used by parents of prospective students in the acceptance of new learners due to the enactment of the zoning system. Parents use fake domicile certificates to get their children into the desired school zoning. A Certificate of Domicile is issued by the competent authorities but the data does not match reality. The purpose of this study is to find out the factors that cause falsification of Domicile Certificates on the registration of new learners with the zoning system, and to find out the application of restorative justice in the legal settlement of falsification of Domicile Certificates on the registration of new learners with a zoning system. Pemalsuan Surat Keterangan Domisili pada pendaftaran peserta didik baru dengan sistem zonasi merupakan suatu bentuk kejahatan digunakan oleh orang tua calon siswa dalam penerimaan peserta didik baru karena diberlakukannya sistem zonasi. Para orang tua menggunakan surat keterangan domisili palsu agar anaknya masuk zonasi sekolah yang diinginkan. Surat Keterangan Domisili dikeluarkan oleh otoritas berwenang namun datanya tidak sesuai dengan kenyataan. Tujuan penelitian ini untuk mengetahui faktor penyebab terjadinya pemalsuan Surat Keterangan Domisili pada pendaftaran peserta didik baru dengan sistem zonasi, dan untuk mengetahui penerapan restoratif justice dalam penyelesaian hukum pemalsuan Surat Keterangan Domisili pada pendaftaran peserta didik baru dengan sistem zonasi.